2022
DOI: 10.3389/fpsyg.2022.752073
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Personality Traits Using Consumer Behavior Patterns in a Virtual Retail Store

Abstract: Virtual reality (VR) is a useful tool to study consumer behavior while they are immersed in a realistic scenario. Among several other factors, personality traits have been shown to have a substantial influence on purchasing behavior. The primary objective of this study was to classify consumers based on the Big Five personality domains using their behavior while performing different tasks in a virtual shop. The personality recognition was ascertained using behavioral measures received from VR hardware, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…However, our data to not support this hypothesis, as neither the gaze-dynamics nor behavioral performance were correlated with WMC (as operationalized here). Other hypotheses regarding the factors contributing to these behaviors, to be tested in future research, include traits such as personality traits, perceptual curiosity, or tendencies of hyperactivity or inattention (Hoppe et al, 2018; Bendall et al, 2021; Maron et al, 2021; Zangrossi et al, 2021; Khatri et al, 2022; Mauriello et al, 2022; Stokes et al, 2022). Regardless of the source of this inter-subject variability, this pattern reminds us that although selective attention studies usually assume that participants allocate their attention ‘as instructed’, in practice overt attention (as well as covert attention) may fluctuate and shift spontaneously, in manners that the experimenters cannot always monitor.…”
Section: Discussionmentioning
confidence: 99%
“…However, our data to not support this hypothesis, as neither the gaze-dynamics nor behavioral performance were correlated with WMC (as operationalized here). Other hypotheses regarding the factors contributing to these behaviors, to be tested in future research, include traits such as personality traits, perceptual curiosity, or tendencies of hyperactivity or inattention (Hoppe et al, 2018; Bendall et al, 2021; Maron et al, 2021; Zangrossi et al, 2021; Khatri et al, 2022; Mauriello et al, 2022; Stokes et al, 2022). Regardless of the source of this inter-subject variability, this pattern reminds us that although selective attention studies usually assume that participants allocate their attention ‘as instructed’, in practice overt attention (as well as covert attention) may fluctuate and shift spontaneously, in manners that the experimenters cannot always monitor.…”
Section: Discussionmentioning
confidence: 99%
“…Agreeableness encapsulates attributes such as empathy, cooperation, and a predisposition toward interpersonal harmony (Shahab et al, 2021). Similarly, Khatri et al (2022) conducted a study examining the relationship between Agreeableness and brand loyalty. Their findings revealed that individuals high in Agreeableness are more likely to develop strong, enduring attachments to brands that align with their values and display ethical practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the existing body of knowledge and research, scholars have extensively discussed consumer behavior in relation to the income and savings of consumers [7]. Similarly, the relevance of cognitive dissonance and socialization theories to consumer behavior has been highlighted in the extant studies [10,11]. Other studies have also focused on the effect of economics and information on sustainable consumer behavior [12].…”
Section: Introductionmentioning
confidence: 99%